Percutaneous closure of symptomatic large tricuspid paravalvular regurgitation using two muscular VSD occluders - Aritra Mukherji; Rajaram Anantharaman; Raghavan Subramanyan (Indian Heart Journal, 2017)
Paravalvular leaks are common following valve replacement surgery. Majority are benign and do not require any active intervention. However, occasionally severe paravalvular regurgitation can produce heart failure and/or hemolysis, needing closure of the defect. It is more commonly associated with aortic and mitral prosthesis, symptomatic tricuspid paravalvular regurgitation being a rare entity. In this report we present the successful percutaneous transcatheter closure of a large paravalvular tricuspid regurgitation in a 59-year old lady with history of multiple previous operations. The elongated crescent-shaped defect was closed using two muscular VSD devices without any residual leak and without hampering the bio-prosthetic tricuspid valve function. Patient had transient complete heart block during the procedure which recovered later. There was marked improvement in the symptomatic status of the patient at discharge (NYHA IV to NYHA II), which was sustained at follow-up.